Digital Technologies and Endogenous Cultures in Niger: Between Preservation and Transformation - Sillimana, Maman (Nurture, 2026)
This article critically examines the complex intersection between endogenous cultural preservation and the rapid penetration of digital technologies,including artificial intelligence (AI), in the Republic of Niger. Situated within the broader context of digital globalization and the country’s significant infrastructural and policy limitations, the study aims to provide a nuanced assessment of both the transformative opportunities and the existential threats that technological integration poses to cultural continuity. Employing a qualitative, document-based analytical approach grounded in Canclini’s seminal theory of cultural hybridization and Castells’ influential network society model, the research explores the multifaceted ways in which information and communication technologies (ICTs) influence the safeguarding, transformation, and dissemination of Nigerien languages, rituals, and artistic expressions. The findings indicate a dualistic impact: digital technologies actively foster the revitalization of cultural heritage through innovative digitization projects, online educational tools, and social media diffusion, while simultaneously heightening the risks of cultural homogenization, decontextualization, and a deepening dependency on foreign digital ecosystems and platforms. The study concludes that sustainable and sovereign cultural preservation in the digital age necessitates a multi-pronged strategy involving equitable technological access, robust digital literacy initiatives, participatory and community-led archiving practices, and reinforced legal and ethical protection of cultural rights. Overall, the article constitutes a significant contribution to the academic discourse on digital globalization by elucidating the specific mechanisms through which African societies—with Niger as a poignant case study—can navigate the delicate balance between embracing technological innovation and protecting their invaluable cultural diversity and sovereignty.